Observing Anterior Crowding In a Population Living a Century Ago - Christopher Cetnar (University Library System, University of Pittsburgh, 2016)
Purpose: To observe the frequency of mandibular anterior crowding in a population who lived during the nineteenth century and compare the rate of occurrence in the current population, which is claimed to be two-thirds of adults experiencing crowding by early adulthood. Materials and Methods: The School of Dental Medicine at the University of Pittsburgh possesses a collection of skulls of individual's likely living in the northeast United States during the late 19th century and early 20th century. Of this skull collection, 29 skulls were evaluated for the presence of mandibular anterior crowding. Results: 55% of the evaluated mandibular anterior arches were positive for mandibular anterior crowding. 57% of the male specimens were positive for anterior crowding, while 50% of the females were recorded to have anterior crowding. These frequencies are lower than the one suggested for the current live population in the United States. Conclusion: From this sample of the population living a century ago, there was a lower prevalence of anterior crowding (55%) than the research suggested two-thirds of adults.